Analisis Numerik Sistem Balok Bataton Semi Pracetak Dengan Variasi Jarak Dan Jumlah Tulangan Sengkang - Prayogo Pratama; Ismeddiyanto Ismeddiyanto; Zulfikar Djauhari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Semi precast concrete or Hybridconcrete construction (HCC) is a structure whose elements system is a combination of precast concrete and cast concretein place or castin place (CIP). Concrete type is in addition to flexural, stirrup reinforcement also need to develop strength. This study examines the behavior of bending and shear, load and deflection relationships, as well as variations in the amount of reinforcement stirrups. Based on the finite element-based numerical analysis, which examined Beams has dimensions of 290 x 140 mm with a length of 3000 mm. Quality precast used 5 MPa while cast in placenya 17.5 Mpa. Variations beam stirrups used without stirrups, stirrups spacing between 0.25 m and 0.15m. The beams are analyzed given the concentrated load at midspan. The analysis showed that the deflection of the beam without stirrups, beams with stirrups spacing between 0.25 m and 0.15 m respectively is 1.396 mm, 1.498 mm and 2.716 mm. Stiffness of the beam without stirrups, beams with stirrups spacing between 0.25 m and beams with stirrups spacing between 0.15 m respectively is 21.489 KN / mm, 21.36 KN / mm, 18.409 KN / mm. The bending moment beam without stirrups, beams with stirrups spacing between 0.25 a m and beams with stirrups spacing between 0.5 m succession is 22.5KNm, 24KNm, 37.5 KNM and third curvature beam models were analyzed in a row was 1.241 / mm, 1.332 / mm , 2.415 / mm.Keywords:Beam,finite element analysis software, semi-precast, stirrups reinforced.